Experimental characterisation of leidenfrost suppression potential of additively manufactured micro/nanoengineered surfaces - Wong, Weng Zhi (Nanyang Technological University, 2024)
This project investigates the droplet dynamics on heated micro/nanostructured aluminium alloys and their performance for Leidenfrost suppression. A conventional aluminium alloy, Al6061, and an additively manufactured (AM) aluminium alloy, AlSi10Mg, were utilised in this investigation. In addition to the plain Al6061 and AM surfaces, through the synergistic use of heat treatment and chemical etching on aluminium alloys, three different microstructure morphologies were fabricated. Furthermore, 300 nm boehmite nanostructures were generated on the plain Al6061 and AM surfaces to produce single tier nanostructures and were incorporated onto the microstructured surfaces to fabricate hierarchical micro/nanostructured surfaces. Hence, a total of 10 test pieces with different surface structure morphologies such as plain, nanostructures, microstructures, and hierarchical micro/nanostructures were investigated in this project. A new experimental setup was also designed and fabricated to investigate the Leidenfrost phenomenon on the micro/nanostructured surfaces.